PENERAPAN STRATEGI PEER TUTORING UNTUK MENINGKATKAN KEMAMPUAN NUMERASI MATEMATIKA PADA MATERI BANGUN RUANG SISI DATAR - Bangun, Bangun; Febryanti, Febryanti; Samad, Irfawandi (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2023)
The background of this research is the lack of mathematical numeracy skills in class VIII students of SMPS Puncak Sumua. This study aims to improve the mathematical numeracy skills of class VIII students as research subjects. This type of research is a type of classroom action research (CAR) with the application of peer tutoring strategies. The data analysis technique in this study is descriptive statistical data analysis. The results showed that the implementation of this strategy could improve students' mathematical numeracy skills as marked by increased student learning outcomes in cycle I and more in cycle II with the average learning outcomes in cycle I is 67.20 and in cycle II is 82.70. Proves that the application of peer tutoring strategies can increase.